Jonah and Qohelet: Satire versus irony - Spangenberg, Izak J. J. (Old Testament essays, 1996)
The literary phenomena irony and satire are often confused and consequently a number of scholars are of the opinion that irony is found in both Jonah and Qohelet. However, a thorough study of satire and irony indicates that Jonah should rather be classified as a satire and Qohelet as containing irony. Satire is directed toward the correction of human behaviour and/or human institutions, whereas the use of irony does not imply change of the status quo. Irony endorses the abundance of insoluble contradictions of life.